Implementation of Green Accounting in Efforts to Realize a Sustainable Green Economy in Banten Province Indonesia: A Case Study of Chemical Companies - Hendrieta Ferieka; Elsa Elsa; Afif Abdillah (Islamiconomic : Jurnal Ekonomi Islam, 2025)
This research comprehensively examines the crucial role of green accounting as a strategic instrument in driving the transition towards a sustainable green economy in Banten Province, Indonesia. By adopting a dominant qualitative approach through a multiple case study on three leading chemical companies in Banten, PT. Lotte Chemical, PT. Chandra Asri Chemical, and PT. Asahimas Chemical, this study analyzes the green accounting practices implemented, the factors influencing them, and their contribution to sustainability. The findings indicate significant variations in the maturity level of green accounting implementation among these companies, which are complexly influenced by top management commitment, government regulatory frameworks, and pressure from various stakeholders. Despite inherent challenges such as limited understanding, data, and clear standards, green accounting practices are proven to contribute substantially to improving resource efficiency, reducing pollution, and enhancing transparency, which are essential pillars for green economic development. This article highlights the urgency of multi-stakeholder collaboration, strengthening regulatory frameworks, and enhancing human resource capacity to accelerate the adoption and effectiveness of green accounting as a catalyst towards a greener and more sustainable future.